PRODUCTION OF CELLULASE ENZYMES USING Bacillus species ISOLATED FROM CASSAVA WASTE - EDORE , Joseph Ailojie; DIMOWO , Courage Gumedia (International Journal of Allied Sciences (IJAS), 2025)
Cellulase enzymes play important roles in the degradation of cellulose. Species from the genus Bacillus that are known for their robust enzyme production, have also been identified as efficient cellulase producers. The aim of this research was to investigate the production of cellulase enzymes using Bacillus species isolated from cassava wastewater. Cassava waste samples were collected aseptically and Bacillus species were isolated using serial dilution and the pour plate method. Characterization and identification were carried out through standard microbiological techniques. Screening for cellulase production was conducted using carboxymethyl cellulose (CMC) agar. Production of cellulase was by submerged fermentation. Enzyme activity was determined using the dinitrosalicylic acid (DNS) assay. The highest and lowest values of the bacteria count recorded across the various wastewater samples were 1.84 ± 0.259 x 107 CFU/mL and 3.7 ± 0.125 x 105 CFU/ml respectively. The isolated Bacillus spp. exhibited significant cellulolytic activity, with clear hydrolysis zones observed on CMC agar. The highest cellulase activity was recorded at 205.71 U/ml under optimized conditions of pH 6.5–7.5 and a temperature of 37°C. This study confirmed the ability of Bacillus spp. to use cassava waste as a cost-effective substrate for enzyme production, highlighting its potential for large- Scale industrial applications.